Vogel and Motulsky's Human Genetics - Speicher, Michael R.; Motulsky, Arno G.; Antonarakis, Stylianos E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The fourth, completely revised edition of this classic reference and textbook presents a cohesive and up-to-date exposition of the concepts, results, and problems underlying theory and practice in human and medical genetics. In the 10 years since the appearance of the third edition, many new insights have emerged for understanding the genetic basis of development and function in human health and disease. Human genetics, with its emphasis on molecular concepts and techniques, has become a key discipline in medicine and the biomedical sciences. The fourth edition has been extensively expanded by new chapters on timely topics such as epigenetics, pharmacogenetics, gene therapy, cloning, and genetic epidemiology, and databases for basic and clinical genetics. In addition a multi/chapter section giving an overview on the main model organisms (mouse, dog, worm, fly, fish) used in human genetics research has been introduced. This book will be of interest to human and medical geneticists, scientists in all biomedical sciences, physicians and epidemiologists, as well as to graduate and postgraduate students who desire to learn the fundamentals of this fascinating field.
History of Human Genetics* -- Human Genome Sequence and Variation -- Chromosomes -- From Genes to Genomics to Proteomics -- Formal Genetics of Humans: Modes of Inheritance* -- Linkage Analysis for Monogenic Traits -- Oligogenic Disease -- Formal Genetics of Humans: Multifactorial Inheritance and Common Diseases -- Lessons from the Genome-Wide Association Studies for Complex Multifactorial Disorders and Traits -- Epigenetics -- Human Gene Mutation: Mechanisms and Consequences -- Human Hemoglobin -- Human Genetics of Infectious Diseases -- Gene Action: Developmental Genetics -- Cancer Genetics -- The Role of the Epigenome in Human Cancers -- Population Genetic Principles and Human Populations -- Consanguinity, Genetic Drift, and Genetic Diseases in Populations with Reduced Numbers of Founders -- Human Evolution -- Comparative Genomics -- Genetics and Genomics of Human Population Structure -- Genetic Epidemiology -- Pharmacogenetics -- Behavioral Genetics -- The Genetics of Personality -- Mental Retardation and Intellectual Disability -- Genetic Factors in Alzheimer Disease and Dementia -- Genetics of Autism -- The Genetics of Alcoholism and Other Addictive Disorders -- Behavioral Aspects of Chromosomal Variants -- Geneties of Schizophrenia and Bipolar Affective Disorder -- Model Organisms for Human Disorders -- Mouse as a Model for Human Disease -- Caenorhabditis elegans, A Simple Worm: Bridging the Gap Between Traditional and Systems-Level Biology -- Drosophila as a Model for Human Disease -- Human Genetics and the Canine System -- Fish as a Model for Human Disease -- Genetic Counseling and Prenatal Diagnosis -- Gene Therapy -- Cloning in Research and Treatment of Human Genetic Disease -- Genetic Medicine and Global Health -- Genetic Databases -- Databases and Genome Browsers -- Ensembl Genome Browser -- Databases in Human and Medical Genetics.
Keywords: Medicine; Human genetics; Biomedicine; Human Genetics